PERILAKU PETUGAS KEBERSIHAN RUMAH SAKTT DALAM PENGELOLAAN SAMPAH DI RS. NIRMALA SURI SUKOHARJO - Bagoes Widjanarko; Sulistiyani -; Rina Hudayani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2004)
The existence of the waste in hospital will cause negative effect to the hospital staffs and the people around the hospital if it is not good to manage waste. The success of the management of waste is detarmined of the many factors, one of them is the behaviour of the cleaning staffs. The aim of this research is to know  the characteristic of the  cleaning staffs, knowledge, attitude and practice in the management of waste in Nirmala Suri Hospital Sukoharjo. Qualitative method is used in this methode of research and subject of  research is all cleaning staffs of Nirmala Suri hospital as many as 12  persons. The tehnique of collecting data by Focus Group Discussion (FGD)  and indepth  interview. The data analysis is content analysis. The result  of the research has shown that the characteristics of the cleaning staffs  based on age, education and work span are various. The youngest age of  the staffis 2l  and the oldest one is  50. The lower education is  Elementary School and the highest one is Diploma  III. The average of work span of the cleaning staffs is six years. The knowledge of the staffs  about the management of the waste from the process of pilling to the  final process is good enough. The attitude of the staffs in the  management of the waste is positive. In doing the management of the  waste, the cleaning staffs refer to the fixed procedure. However, in doing  the job, the cleaning staffs sometimes do not do it as written on the  fixedprocedure.